"The second woman" = [Otra mujer] - Kern, James V., 1909-1966; Briskin, Mort; Smith, Robert (Screenwriter); Young, Robert, 1907-1998; Drake, Betsy, 1923-2015; Cardinal Pictures; Cinetel Films ([Los Angeles, CA] : Cardinal Pictures, Inc., 1950)
Ellen (Betsy Drake) meets a stranger on a train (Robert Young) and is immediately taken by his charm. She soon discovers that his wife was mysteriously killed on their honeymoon and he is haunted by dark visions of her death.
Originally released as a motion picture in 1950 by United Artists.
Robert Young, Betsy Drake, John Sutton, Florence Bates, Morris Carnovsky, Henry O'Neill, Hean Rogers, Raymond Largay.
Cinematographer, Hal Mohr; editor, Walter Thompson; musical themes, Peter Ilyitch Tschaikovsky ; orchestrations, Joseph Nussbaum; adaptation and musical direction, Nat W. Finston.
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Railroad travel -- Drama; Widowers -- Drama; Detective and mystery films; Feature films; Internet videos; Streaming video